Teachers' pedagogical attitude on using digital lesson contents in teaching and learning in Zanzibar secondary schools - Ali Juma Hamad; Placidius M. Ndibalema; Kulwa Yohana Matalu (Academy of Cognitive and Natural Sciences, 2024)
Digital curricula have been emphasized to improve the quality of education at all levels of education. Implementing a new curriculum depends on teachers' attitudes to integrate it during teaching and learning. This study investigated the attitudes of teachers and factors that affect them towards using digital lesson content in Zanzibar, the case of Wete District. One hundred fifty-four secondary school teachers responded to the questionnaire. The SPSS version 25 was used to run the Chi-squared test and descriptive statistics to analyse the data. The overall attitude was calculated by finding the questions' mean value per Likert level. The study found that teachers' pedagogical attitude is positive, but implementing digital lesson content in Zanzibar is still challenging. It was also observed that the attitude was significantly associated with gender (p=0.0084), whereby female respondents had higher positive attitudes (68.82%) compared to male respondents (47.44%). The paper concludes that most teachers have a positive attitude towards using digital lesson content in teaching in secondary schools. However, they lack enough relevant digital resources that support digital lesson content. Based on that, policymakers, curriculum developers, and other education stakeholders should take serious action to improve the quality of education practice in Zanzibar. Therefore, this paper recommends that the availability of digital lesson content and in-service training may encourage teachers' pedagogical attitude to integrate digital materials into their everyday teaching process.